Trabalho infanto-juvenil no uso do manguezal e a educação fundamental - BLANDTT, Lucinaldo da Silva (2002)
Work of 6 to 14 years old children is important for the survival of their families, however, it does not contribute to the monetary family income that based upon commercial fisheries, crab processing and agriculture. From an age of 4 years onwards children are encouraged to work by their parents. However, only 7 years old boys and 5 years old girls contribute significantly to the subsistence of their families. From an age of 14 years parents push their children to earn money by selling products to local agents. For teenagers remunerated work is indispensable for self support. 40% of the children between 7 and 14 years work instead of going to school which is a big obstacle for their education. The socio-economic and educational situation of children and teenagers living in the Bragança area may be improved by the process of participation and transdisciplinarity, as an effective sustainability element, as it may allow them to escape from the poverty cycle that their families are part of far generations.